Frequency-coded patterns of sympathetic vasomotor activity are differentially evoked by the paraventricular nucleus of the hypothalamus in the Goldblatt hypertension model - Faber, Jean; Milanez, Maycon I. O.; Simões, Cristiano S.; Campos, Ruy R. (Frontiers in Cellular Neuroscience, 2023)
The paraventricular nucleus of the hypothalamus (PVN) contains premotor neurons involved in the control of sympathetic vasomotor activity. It is known that the stimulation of specific areas of the PVN can lead to distinct response patterns at different target territories. The underlying mechanisms, however, are still unclear.Recent evidence from sympathetic nerve recording suggests that relevant information is coded in the power distribution of the signal along the frequency range. In the present study, we addressed the hypothesis that the PVN is capable of organizing specific spectral patterns of sympathetic vasomotor activation to distinct territories in both normal and hypertensive animals. We investigated the territorially differential changes in the frequency parameters of renal and splanchnic sympathetic nerve activity (rSNA and sSNA, respectively), before and after disinhibition of the PVN by bicuculline microinjection, in control and Goldblatt rats, a model of hypertension (2K1C). Additionally, considering the importance of angiotensin II type 1 receptors (AT1) in the sympathetic responses triggered by bicuculline in the PVN, we also investigated the impact of angiotensin AT1 receptors blockade in the spectral features of the rSNA and sSNA activity. The results revealed that each nerve activity (renal and splanchnic) presents its own electrophysiological pattern of frequencycoded rhythm in each group (control, 2K1C and 2K1C treated with AT1 antagonist losartan) in basal condition and after bicuculline microinjection, but with no significant differences regarding total power comparison among groups. Additionally, the losartan 2K1C treated group showed no decrease in the hypertensive response triggered by bicuculline when compared to the non-treated 2K1C group. However, their spectral patterns of sympathetic nerve activity were different from the other two groups (control and 2K1C), suggesting that the blockade of AT1 receptors does not totally recover the basal levels of neither the autonomic responses nor the electrophysiological patterns in Goldblatt rats, but act on their spectral frequency distribution. In conclusion, the results suggest that the differential responses evoked by the PVN were preferentially coded in frequency but not in the global power of the vasomotor sympathetic responses, indicating that the PVN is able to independently control the frequency and the power of sympathetic discharges.